Different Executive Functions Support Different Kinds of Cognitive Flexibility: Evidence From 2‐, 3‐, and 4‐Year‐Olds. Issue 2 (11th December 2015) - Blakey, Emma; Visser, Ingmar; Carroll, Daniel J.
Abstract : Improvements in cognitive flexibility during the preschool years have been linked to developments in both working memory and inhibitory control, though the precise contribution of each remains unclear. In the current study, one hundred and twenty 2‐, 3‐, and 4‐year‐olds completed two rule‐switching tasks. In one version, children switched rules in the presence of conflicting information, and in the other version, children switched rules in the presence of distracting information. Switching in the presence of conflict improved rapidly between the ages of 3 and 3.5 years, and was associated with better working memory. Conversely, switching in the presence of distraction developed significantly between the ages of 2 and 3 years, and was associated with better inhibitory control.